Efektivitas Pembelajaran Student Teams Achievement Divisions (STAD) - Virtual Flipped Classroom - sasomo budi; Arum Rahmawati (Universitas Sarjanawiyata Tamansiswa, 2022)
The thing that forms the basis of this activity is to determine the effectiveness of the STAD virtual flipped classroom learning implementation. The t test was chosen to be used in analyzing the data resulting from research activities. The t-test describes the difference in learning outcomes for the class before being treated with the STAD virtual flipped classroom after being given treatment. The difference between students who were given the STAD virtual flipped classroom learning treatment can be seen by comparing their average scores. The class learning outcomes before being given the STAD virtual flipped classroom learning treatment were 73.47. Class learning outcomes after being subjected to STAD virtual flipped classroom learning are 82.61. This shows that the class that has been given the STAD virtual flipped classroom learning treatment has better learning outcomes. STAD virtual flipped classroom learning is carried out with the stages of material being studied by students first, then followed by discussions in limited face-to-face meetings in class. Virtual teaching and learning activities are carried out through direct interaction between lecturers and students using video conferencing applications that promote collaboration between students, provide mutual motivation and have an active role as peer tutors. So the implementation of teaching and learning activities using the STAD virtual flipped classroom can provide students with increased learning outcomes and create a learning atmosphere that students will always miss.